Efektivitas Sistem Informasi Prestasi Mahasiswa (SIPRESMA) dalam Pengelolaan Data Prestasi Mahasiswa UKM Pelita di Universitas Tidar - Khorin Noor Latifah; Izzatul Yazidah; Oktavia Ramadhani; Tiara Novita Sari; Ranti Nisrina Mufidah (Jurnal Publikasi Teknik Informatika, 2026)
This study aims to analyze the effectiveness of the Student Achievement Information System (SIPRESMA) in managing student achievement data of UKM Pelita at Universitas Tidar. The study employed a quantitative approach with a descriptive research method. The population consisted of 305 members of UKM Pelita, with a sample of 76 respondents determined using the Slovin formula with a 10% margin of error. The sampling technique used was simple random sampling. Data collection was conducted through questionnaires based on the DeLone and McLean Information System Success Model, which includes system quality, information quality, service quality, use, user satisfaction, and net benefits. Data analysis was carried out using validity tests, reliability tests, descriptive analysis, t-tests, and the coefficient of determination (R²) with the assistance of IBM SPSS Statistics. The results showed that all questionnaire items were valid and reliable. The hypothesis testing results indicated a significance value of <0.001, meaning that the effectiveness of SIPRESMA has a positive and significant effect on the management of student achievement data of UKM Pelita at Universitas Tidar. The coefficient of determination (R²) value of 0.660 indicates that the effectiveness of SIPRESMA explains 66% of the variation in student achievement data management, while the remaining 34% is influenced by other factors outside the study. Overall, SIPRESMA is considered capable of facilitating data management, improving work efficiency, accelerating access to information, and providing user satisfaction. However, several issues such as system stability, service responsiveness, and consistency of data updates still need improvement to optimize the effectiveness of the system.